Knot formation by Pseudomonas syringae subsp. savastanoi on the in vitro shoots of Sorbus redliana - Hevesi, M.; Papp, J.; Jámbor-Benczúr, E.; Gazdag, Gy. (International Journal of Horticultural Science, 1999)
Two strains of Pseudomonas syringae subsp. savastanoi were isolated from Forsythia sp. and Nerium oleander in Hungary in 1997. The effects of growth regulators produced by the bacteria were studied in different experiments. The strains were co-cultured with Sorbus redliana in vitro shoots without being in contact with the plant on solid media. Further culture filtrates in different concentrations were added to the culture medium. The growth regulators presented in the agar caused knot formation on the shoots and on the leaves in both kinds of culture. There were significant differences in the cultural and physiological characters, auxin and cytokinin activity of the strains of different origin.